A Pattern of Organization Management of Entrepreneurial Bugis Merchants Rice Trade in South Sulawesi, Indonesia - S.E, Ansar (Asian Journal of Social Sciences and Management Studies, 2017)
This research analyzes the pattern of organization management of entrepreneurial Bugis merchants in South Sulawesi rice trade in ancient times. As for who became informants in this study was the Bugis traders who are still active and which is not a longer active trade of rice. This research is a descriptive analysis using qualitative approach through case studies, but the results of this study indicate that the majority of the Bugis merchants ever existed of his time and experience the ups and downs at the development time and intense competition, technology management and entrepreneurship. They are able to survive long is that implementing the principles of good management with i.e. planning, organizing, and monitoring the movement of the. In addition to that aspect of human resources play an important role in the process of developing the quality of thought, affecting every aspect of action, behavior in building interaction with each other both locally, nationally and internationally, so that this is causing the position of merchants Bugis have competitiveness and different characteristics with other merchants in the field first.